Inglés Intermedio I - Rendón Fragoso, Rogelio (My University, 2006)
INDICE Practice 1 Introduce yourself. Practice 2 Introduce other people. Practice 3 Ask someone where he´s /she´s from. Tell someone where you´re from. Practice 4 Write ´m, ´s or ´re. Practice 5 Open conversation. Practice 6 Find the owner. Practice 7 Do the crossword puzzle.
Keywords: Inglés intermedio I; Hi, hey, hello, good morning, good afternoon, good evening, my name´s, this is, nice to meet you, where are you from?, I´m from, what about you?, (hello, my name is), I´m, we´re, I´m from, she´s from, his, her, this, that, these, those, are, aren´t